LANGUAGE GAMES AND CULTURAL ARTIFACTS: CONVERGENCES BETWEEN LUDWIG WITTGENSTEIN AND MICHEL DE CERTEAU (Interdisciplinary Studies Journal, 2024)
This article explores the intersections between the intellectual works of Ludwig Wittgenstein (1889 – 1951) and Michel de Certeau (1925 – 1986), focusing on the concepts of 'language games' and 'cultural artifacts'. Through a literature review, we will examine how these concepts relate and how the intellectual trajectories of both authors contributed to their formulations. The objective is to demonstrate that the notion of cultural artifact converges with that of language games, offering new perspectives for both philosophy and cultural studies.
Keywords: Michel de Certeau; Ludwig Wittgenstein; Culture; Language